2018
DOI: 10.1186/s12920-018-0434-y
|View full text |Cite
|
Sign up to set email alerts
|

An isomiR expression panel based novel breast cancer classification approach using improved mutual information

Abstract: BackgroundGene expression-based profiling has been used to identify biomarkers for different breast cancer subtypes. However, this technique has many limitations. IsomiRs are isoforms of miRNAs that have critical roles in many biological processes and have been successfully used to distinguish various cancer types. Biomarker isomiRs for identifying different breast cancer subtypes has not been investigated. For the first time, we aim to show that isomiRs are better performing biomarkers and use them to explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 43 publications
(43 reference statements)
0
16
0
Order By: Relevance
“…More recently, Wang and colleagues used the same data to demonstrate that isomiRs that share their seed region (5 isoforms) could similarly discriminate between tumors [70]. In 2018, Lan and colleagues published the first study to use breast cancer TCGA small RNA sequencing expression data to show that the isomiR expression-based classification was superior to gene expression profiling at distinguishing between breast cancer subtypes [71]. Together these findings suggest that miRNAs may carry out significant functional roles in tumorigenesis at the isomiR level.…”
Section: Isomirs and Their Emerging Significance In Cancermentioning
confidence: 99%
“…More recently, Wang and colleagues used the same data to demonstrate that isomiRs that share their seed region (5 isoforms) could similarly discriminate between tumors [70]. In 2018, Lan and colleagues published the first study to use breast cancer TCGA small RNA sequencing expression data to show that the isomiR expression-based classification was superior to gene expression profiling at distinguishing between breast cancer subtypes [71]. Together these findings suggest that miRNAs may carry out significant functional roles in tumorigenesis at the isomiR level.…”
Section: Isomirs and Their Emerging Significance In Cancermentioning
confidence: 99%
“…IsomiRs are functionally important and have distinct roles in tissue-specific gene regulation [203]. Furthermore, isomiR expression changes in disease and when compared to canonical miRNAs, can better classify different tumour types [204,205]. Therefore, the specificity of diagnostic and prognostic panels could be considerably improved if isomiRs were also tested for their suitability as biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that the presence of 5 isomiRs could effectively classify 32 different tumor types with more than 90% sensitivity [150,155]. Findings from Telonis et al [149] and Lan et al [156] support the advantages of using isomiRs in the classification of breast cancer subtypes compared with protein-coding gene expression. High levels of isomiRs hsa-let-7i-5p | 3 a-1 and hsa-miR-197-3p | 3 a-1 have been found in ER negative tumors, but not in ER positive tumors [156].…”
Section: Isomirs Add Tremendous Diversity To Mirna Species and Targetmentioning
confidence: 96%
“…High levels of isomiRs hsa-let-7i-5p | 3 a-1 and hsa-miR-197-3p | 3 a-1 have been found in ER negative tumors, but not in ER positive tumors [156]. On the other hand, the 5 isomiR hsa-miR-93-5p | 5 t-1 disrupts the estrogen signalling pathway by targeting SHC4, while hsa-miR-27a-3p | 5 t-1, hsa-miR-92a-1-3p | 5 -1, and hsa-miR-106b-3p | 5 t-1 interfere with mitogen-activated protein kinase (MAPK) signalling by targeting MAPK14, MAPK8, and RAP1B, respectively, in the ER positive tumors, showing the high specificity of these isomiRs in cancer subtype classification [156].…”
Section: Isomirs Add Tremendous Diversity To Mirna Species and Targetmentioning
confidence: 98%
See 1 more Smart Citation